Faktor- faktor yang berpengaruh terhadap audit judgment (studi empiris pada Badan Pemeriksa Keuangan (BPK) RI perwakilan provinsi Riau) - Rida MM Siagian; Hardi '; Al-azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to examine the influence of gender , experience of the auditor , the auditor's knowledge , obedience pressure and task complexity in the making audit judgment.The samples in this study were all auditors working at the Supreme Audit Agency ( BPK ) RI Riau Province . Methods of data collection in this study is the method of questionnaire survey using instruments that are delivered directly to the Supreme Audit Agency ( BPK ) RI Representative Riau Province . The Respondents are used in the analysis were 43 respondents ( 81.3 % ) . Methods of Analysis is conducted with a multiple regression analysis using SPSS (Statistical Product and Service Solutions ) Version 17.The results of hypothesis testing using t-test , concluded H1 , H2 , H3 , H4 is accepted which has a significance value p - value < 0.5 , indicating that the gender variable , auditor experience , knowledge of the auditor , and obedience pressure has an influence on the auditor's judgment audit The Supreme Audit Agency ( BPK ) RI Representative Riau province . While the complexity of the task variable has a significance value p-value > 0.5 , H5 is not acceptable . The coefficient of determination in this study was 78 % . These four variables affect the dependent variable was 78 % , while 22 % is influenced by other variables that are not addressed in this study .Keywords : Audit Judgment , Gender , Auditor Experience , Knowledge Auditor , Obedience Pressure , Task Complexity.